Plasma and Pancreas Islet Hormone Concentrations in Lactating Rats Are Associated with Dietary Protein Amounts. Issue 3 (12th March 2018) - Xu, Lianbin; Lin, Xueyan; White, Robin R; Hanigan, Mark D; Hu, Zhiyong; Hou, Qiuling; Wang, Yun; Wang, Zhonghua
Abstract: Background: Circulating amino acid (AA) and nitric oxide (NO) concentrations and hepatic gluconeogenesis are affected by previous protein intake. However, information about their relations and islet hormone responses is limited. Objective: This study investigated the associations between islet hormone concentrations with circulating AA and NO concentrations as well as with hepatic gluconeogenesis in lactating rats. Methods: At delivery, 18 Wistar rats aged 14 wk were assigned either to low-protein (LP; 9% protein), standard-protein (SP; 21% protein), or high-protein (HP; 35% protein) diets for 15 d in groups of 6 pups/dam. Circulating AA and NO concentrations, circulating and pancreas islet hormone concentrations, and the activities and gene expressions of hepatic phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase) were measured at the end of treatment. Results: Circulating insulin and glucagon concentrations were greater in the HP than in the LP (25% and 17%, respectively) and SP (37% and 31%) diet groups, whereas compared with the SP group, pancreatic concentrations were lower in the LP (32% and 49%) and HP (34% and 46%) groups ( P < 0.01). Hepatic PEPCK and G6Pase activities in the HP group were greater than those in the SP (15% and 15%) and LP (8% and 19%) groups ( P < 0.05). In all groups, plasma NO concentrations were correlated negatively to circulating insulin ( r = −0.77, P = 0.0003) and positively to pancreas insulin and glucagon concentrations and the insulin-to-glucagon ratio ( r = 0.50–0.63; P < 0.05). Some circulating AAs correlated positively to circulating insulin and pancreas insulin and glucagon ( r = 0.50–0.82, P < 0.05) but negatively to circulating glucagon ( r = −0.53–0.68, P < 0.05). Conclusion: Variations in circulating AA and NO concentrations and hepatic gluconeogenic enzyme activities are likely intermediary responses involved in the effects of dietary protein amounts on the synthesis and secretion of islet hormones in lactating rats.